SCRAPBOOK TO INTRODUCE ALPHABET: A DEVELOPMENT RESEARCH FOR PRESCHOOL LEARNERS - Diana Dwi Shopiyana; Ikhsanudin Ikhsanudin; Eni Rosnija (University of Muhammadiyah Malang, 2021)
This study was to develop a Scrapbook to introduce Alphabet for preschool learners. This research involved the teachers in Darul Uloom Kindergarten Pontianak Kota. The method of this research was development research which consists of three phases of ADDIE (analyze, design, and develop). The product is to introduce the Alphabet in an interesting and attractive way for preschool learners. The need analysis obtained the information of what the teacher and students need in teaching and learning the Alphabet by identifying the analysis of the teacher and the students' condition. The design of the Scrapbook focused on the criteria of the appropriate material, selecting the suitable decorations, and using the appropriate pictures and details in designing Scrapbook. The Construction of Scrapbook contains of 26 letter names and letter sounds. The model of Scrapbook is using a hard cover album, which consists of 26 letters and its phonetics as the main material. The product was also designed with the appropriate layouts, such as paper size, pictures' management (cropping and resizing), colors, shapes, and fonts in order to produce the product with the suitable standard of printing. The development of Scrapbook described what the constructs of the product were, including the fonts of the Alphabet, layout designs, contents, and teachers' validation. The result is the complete product of Scrapbook considered as very good and feasible to be used as a teaching and learning media to introduce Alphabet for preschool learners.